No-Touch Versus Conventional Vein Harvesting Techniques at 12 Months After Coronary Artery Bypass Grafting Surgery: Multicenter Randomized, Controlled Trial. Issue 14 (5th October 2021) - Tian, Meice; Wang, Xianqiang; Sun, Hansong; Feng, Wei; Song, Yunhu; Lu, Feng; Wang, Liqing; Wang, Yang; Xu, Bo; Wang, Huaibin; Liu, Su; Liu, Zhigang; et al.
Abstract : Background: Vein graft occlusion is deemed a major challenge in coronary artery bypass grafting. Previous studies implied that the no-touch technique for vein graft harvesting could reduce occlusion rate compared with the conventional approach; however, evidence on the clinical benefit and generalizability of the no-touch technique is scare. Methods: From April 2017 to June 2019, we randomly assigned 2655 patients undergoing coronary artery bypass grafting at 7 hospitals in a 1:1 ratio to receive no-touch technique or conventional approach for vein harvesting. The primary outcome was vein graft occlusion on computed tomography angiography at 3 months and the secondary outcomes included 12-month vein graft occlusion, recurrence of angina, and major adverse cardiac and cerebrovascular events. The generalized estimate equation model was used to account for the cluster effect of grafts from the same patient. Results: During the follow-up, 2533 (96.0%) participants received computed tomography angiography at 3 months after coronary artery bypass grafting and 2434 (92.2%) received it at 12 months. The no-touch group had significantly lower rates of vein graft occlusion than the conventional group both at 3 months (2.8% versus 4.8%; odds ratio, 0.57 [95% CI, 0.41–0.80]; P <0.001) and 12 months (3.7% versus 6.5%; odds ratio, 0.56 [95% CI, 0.41–0.76]; P <0.001). Recurrence of angina was also less common in the no-touch group at 12 months (2.3% versus 4.1%; odds ratio, 0.55 [95% CI, 0.35–0.85]; P <0.01). Rates of major adverse cardiac and cerebrovascular events were of no significant difference between the 2 groups. The no-touch technique was associated with higher rates of leg wound surgical interventions at 3-month follow-up (10.3% versus 4.3%; odds ratio, 2.55 [95% CI, 1.85–3.52]; P <0.001). Conclusions: Compared with the conventional vein harvesting approach in coronary artery bypass grafting, the no-touch technique significantly reduced the risk of vein graft occlusion and improved patient prognosis. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03126409. Abstract : Supplemental Digital Content is available in the text.